The influence of symbiotic bacteria on reproductive strategies and wing polyphenism in pea aphids responding to stress - Reyes, Miguel L; Laughton, Alice M; Parker, Benjamin J; Wichmann, Hannah; Fan, Maretta; Sok, Daniel; Hrček, Jan; Acevedo, Tarik; Gerardo, Nicole M (The Journal of animal ecology, 2019)
Environmental stressors can be key drivers of phenotypes, including reproductive strategies and morphological traits. The response to stress may be altered by the presence of microbial associates. For example, in aphids, facultative (secondary) bacterial symbionts can provide protection against natural enemies and stress induced by elevated temperatures. Furthermore, aphids exhibit phenotypic plasticity, producing winged (rather than wingless) progeny that may be better able to escape danger, and the combination of these factors improves the response to stress. How symbionts and phenotypic plasticity, both of which shape aphids' stress response, influence one another, and together influence host fitness, remains unclear. In this study, we investigate how environmental stressors drive shifts in fecundity and winged/wingless offspring production, and how secondary symbionts influence the process. We induced production of winged offspring through distinct environmental stressors, including exposure to aphid alarm pheromone and crowding, and, in one experiment, we assessed whether the aphid response is influenced by host plant. In the winged morph, energy needed for wing maintenance may lead to trade-offs with other traits, such as reproduction or symbiont maintenance. Potential trade-offs between symbiont maintenance and fitness have been proposed but have not been tested. Thus, beyond studying the production of offspring of alternative morphs, we also explore the influence of symbionts across wing/wingless polyphenism as well as symbiont interaction with cross-generational impacts of environmental stress on reproductive output. All environmental stressors resulted in increased production of winged offspring and shifts in fecundity rates. Additionally, in some cases, aphid host-by-symbiont interactions influenced fecundity. Stress on first-generation aphids had cross-generational impacts on second-generation adults, and the impact on fecundity was further influenced by the presence of secondary symbionts and presence/absence of wings. Our study suggests a complex interaction between beneficial symbionts and environmental stressors. Winged aphids have the advantage of being able to migrate out of danger with more ease, but energy needed for wing production and maintenance may come with reproductive costs for their mothers and for themselves, where in certain cases, these costs are altered by secondary symbionts.
Keywords: pea aphid; Symbiosis; křídla zvířecí; trade-offs; life history; environmental stressors; hrách setý; Bacteria; Animals; symbiosis; Aphids; Pisum sativum; symbióza; zvířata; mšice; phenotypic plasticity; Wings, Animal